Vein wrapping promotes M2 macrophage polarization in a rat chronic constriction injury model. Issue 8 (23rd March 2018) - Hirosawa, Naoya; Uchida, Kentaro; Kuniyoshi, Kazuki; Murakami, Kenichi; Inoue, Gen; Miyagi, Masayuki; Matsuura, Yusuke; Orita, Sumihisa; Inage, Kazuhide; Suzuki, Takane; Takaso, Masashi; Ohtori, Seiji
ABSTRACT: Although the therapeutic potential of vein wrapping (VW) for recurrent compressive neuropathy has been widely reported, the mechanisms underlying this technique have not been characterized. M2 macrophages induced by interleukin‐4 (IL‐4) or interleukin‐10 (IL‐10) have an anti‐inflammatory function and play an important role in peripheral nerve repair. To evaluate whether VW promotes M2 polarization, we divided chronic constriction injury (CCI) rats into untreated and VW (CCI + VW)‐treated groups. Pain withdrawal thresholds in both groups were evaluated using von Frey filaments. Expression of the anti‐inflammatory cytokines IL‐4 and IL‐10 in vein and nerve were quantified using real time polymerase chain reaction (RT‐PCR), and expression of the anti‐inflammatory M2 macrophage markers CD206 and arginase‐1 (Arg1) after VW was assessed by RT‐PCR and immunohistochemistry. To evaluate the effect of exogenous IL‐4 or IL‐10 on M2 macrophage‐marker expression, CD11b‐positive macrophages isolated from sciatic nerve were stimulated with recombinant IL‐4 and IL‐10. VW significantly increased the pain withdrawal threshold. IL‐4 and IL‐10 mRNA expression was higher in veins than in the sciatic nerve. VW significantly increased CD206 and Arg1 mRNA expression compared to the CCI group. The number of CD206‐ and Arg1‐immunoreactive cells in nerve bundles was twofold higher in the CCI + VW than CCI group. Application of exogenous IL‐4 doubled CD206 and Arg1 mRNA expression in CD11b‐positive macrophages. These results show that vein‐derived IL‐4 potentiates the benefit of VW through the activation of M2 macrophages in the sciatic nerve. Our results may help to optimize current procedures for treating recurrent compressive neuropathy. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2210–2217, 2018.